An indicator of the view of time passing: the development and validation of the metacognitive knowledge of time passing scale (MKTPS) in Chinese college students - Yu, Xide; Lu, Cheng; Ma, Yaju; Huang, Li; Wu, Chenyang (Frontiers in Psychology, 2024)
How we view the passage of past time determines how we face time itself as well as our futures, which has a strong impact particularly during the highly creative and malleable college years. Chinese culture cherishes time deeply, and for centuries there has been a tradition of “educating children and youth to inspect the passage of time”. However, in today’s age of information and intelligence, time has shown a trend toward fragmentation. How do contemporary Chinese college students view the passage of time, and what structures or content does it contain? The answer to this question remains uncertain, necessitating further exploration. Following Flavell’s theory of metacognitive knowledge (MK), we adopted a semi-structured interview method and used the results to first outline the basic structure of Chinese college students’ view of time passing, identifying four major aspects: priming aftereffect, life touching, positive promotion, and negative inhibition. Then, using the initial four-dimensional structure as a starting point, we developed the Metacognitive Knowledge of Time Passing Scale (MKTPS), and carried out exploratory factor analysis and confirmatory factor analysis to test its fit. The results showed that the four-factor scale and its 22 items had a good fit to the data. Third, the reliability and validity of the self-developed scale were tested. The results show that the internal consistency, split-half, and retest reliability of the MKTPS are good (all rs >0.60). The construct validity of the MKTPS is also good (rbetween subscales is 0.33-0.60, rbetween subscales and total scale is 0.64-0.87), the convergent validity with Zimbardo’s negative past time perspective is high (r = 0.37), and the discriminant validity with Zimbardo’s future time perspective is significant (r = 0.18). Regarding criterion correlation validity, the total scores of the MKTPS have a significantly higher positive correlation with those of the time management disposition (TMD) scale (r = 0.45). Future points for studying the view of time passing in adults of all ages and across cultures field and shortcomings of the current study are also discussed.